ПРОБЛЕМЫ УСТОЙЧИВОГО РАЗВИТИЯ СЕЛА И ПУТИ ИХ РЕШЕНИЯ - Сапарова, Г К; Булхаирова, Ж С (Journal of Economic Research & Business Administration, 2015)
In article it has been considered agrarian sector by authors, namely the huge role has been noted country and its influence on developments RК, considered a current state of rural settlements, problems of a sustainable development of rural territories are allocated and shown what attempts for elimination of the given problems are undertaken.